Copper(II) Complexes with Tridentate Bis(pyrazolylmethyl)pyridine Ligands: Synthesis, X‐ray Crystal Structures and ϵ‐Caprolactone Polymerization. Issue 30 (25th October 2017) - Rueda‐Espinosa, Juan; Torres, Juan F.; Gauthier, Carmen Valdez; Wojtas, Lukasz; Verma, Gaurav; Macías, Mario A.; Hurtado, John
Abstract: Reactions of Cu(ClO4 )2 ⋅6H2 O with 2, 6‐bis(3, 5‐dimethylpirazol‐1‐ylmethyl)pyridine (dmpz‐py) (1 ), 2, 6‐bis(4‐iodo‐3, 5‐dimethylpirazol‐1‐ylmethyl)pyridine (I‐dmpz‐py) (2 ) and 2, 6‐bis(4‐nitro‐3, 5‐dimethylpirazol‐1‐ylmethyl)pyridine (NO2 ‐dmpz‐py) (3 ) yield the corresponding metal complexes: [Cu(dmpz‐py)(H2 O)(ClO4 )]ClO4 (4 ), [Cu(I‐dmpz‐py)(H2 O)](ClO4 )2 (5 ) and [Cu(NO2 ‐dmpz‐py)(H2 O)(ClO4 )2 ] (6 ). The complexes were isolated in high yields as stable solids at room temperature and characterized by melting point, electrical conductivity, and infrared and ultraviolet/visible spectroscopy. In addition, the crystal structures of the new complexes were determined by single‐crystal X‐ray diffraction and showed square‐base pyramidal (4 ), distorted square‐planar (5 ) and octahedral (6 ) geometries. All three complexes were active in the ring opening polymerization of ϵ‐caprolactone under solvent‐free conditions, producing polycaprolactones of narrow polydispersity and high crystallinity. The results obtained show an important increase in polymerization speed compared with analogous azole‐derived copper (II) complexes. Abstract : Three copper (II) complexes with bis(pyrazolylmethyl)pyridine derived ligands were synthesized and its structure were determined using X‐ray single crystal analysis. All complexes are good initiators for ϵ‐caprolactone polymerization under solvent free conditions, with a significantly higher velocity than most of the azole‐derived copper (II) complexes reported. The obtained polymer shows narrow polydispersity and high crystallinity in all cases.